A case of infectious pericardial effusion and tamponade in a guinea pig (Cavia porcellus) associated with a multiresistant staphylococcus. Issue 1 (2nd June 2014) - Quinton, Jean‐François; Valentin, Suzy; Ruel, Yannick
Abstract : A three‐year‐old female guinea pig was presented for an acute onset of lethargy and dyspnoea and was subsequently diagnosed with pericardial effusion and cardiac tamponade. Bacterial culture of the fluid obtained from ultrasound‐guided pericardiocentesis revealed a coagulase‐negative multiresistant staphylococcus. Pericardiocentesis and antibiotic therapy resulted in complete resolution of the pericardial effusion. As the staphylococcus was resistant to many antibiotics and the owner was diagnosed a few weeks prior with cutaneous multiresistant staphylococcal infection, it was speculated that the source of the septic pericardial effusion may have been the owner.